Socio-economic substantiation of expediency of seasonal influenza vaccine prophylaxis among medical workers - Kyi-Kokarieva, V.G.; Kriachkova, L.V.; Padalkо, L.I. (Medicni Perspektivi, 2021)
The purpose of this study is to determine the socio-economic effectiveness of seasonal influenza vaccine prophylaxis among health professionals based on the analysis of the morbidity with temporal disability (MTD) and the financial benefits of this preventive measure. The study included the collection and analysis of information on MTD and direct and indirect costs of influenza treatment compared to vaccine prophylaxis in “Dnipropetrovsk Regional Perinatal Center with Hospital” Dnipropetrovsk Regional Council” (ME “DRPC with Hospital” DRC”) during 2017-2020 (3 epidemic seasons). To assess the consequences of vaccine prophylaxis, the analysis of MTD indicators was performed, and the index and coefficient of anti-epidemic effectiveness were used. The economic effect was determined on the basis of the cost-benefit method using the analysis algorithm in the form of a “decision tree”. The information base for the analysis was the accounting and reporting and financial and economic documentation of the health care institution (HCI). The analysis of influenza MTD during the observation period revealed that all studied morbidity rates (number of cases per 100 employees; number of days per 100 employees; average case duration) were statistically significantly lower in vaccinated compared to unvaccinated (p<0.001). Precautionary number of cases of MTD for influenza in the last year of observation (2019-2020) was 11.07 (95% CI 6.68-15.46) per 100 employees; days – 96.23 (95% CI 81.86-110.60) per 100 employees. The index of anti-epidemic efficiency during the study increased by 2.37 (95% CI 1.95-2.79), the coefficient of anti-epidemic effectiveness – by 15.16% (95% CI 11.17-18.01). The economic efficiency of vaccination of 69.44% of employees for one epidemic season (2019-2020) amounted to a total of UAH 248,976 or UAH 494 (56%) benefits per employee. The study proved the high medical, social and economic effectiveness of vaccine prophylaxis in HCI. Medical efficiency consists in a significant reduction in the morbidity with temporary disability, high levels and a tendency to increase the indicators of anti-epidemic efficiency. The economic effect is defined as the available monetary benefit from the vaccine prophylaxis. The resulting savings are the basis for optimizing the use of resources of the medical institution, including labor.